ANALYSIS OF RISK FACTORS CAUSING DIABETES MELITUS IN WOMEN OF PRODUCTIVE AGE (15-49 YEARS) IN THE SUKAKARYA COMMUNITY HEALTH CENTER WORKING AREA KOTA SABANG IN 2020 - Febriyanti, Heni; Fahdhienie, Farrah; Marzuki, Marzuki (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: The prevalence of Diabetes melitus (DM) in women of productive-age (15-49 years) has increased in cases from 2018 by 4.5% to 6.8% in 2019 and in 2020 from January-March by 7%. Research objectives: to determine the risk factors that cause DM in women of productive age in the working area of the Sukakrya Health Center, Kota Sabang in 2020. Methods: This research design uses case-control. The population of this study were DM sufferers and not DM sufferers in women of productive age 15-49 years in the working area of the Sukakarya Health Center, Kota Sabang. The sample consisted of a case sample of 57 respondents and a control sample of 57 respondents. Data collection was carried out from November 23 to December 21, 2020. Data were analyzed using the Chi-Square test with the SPSS 21 program. Results: The results showed that women of productive age who had a family history of DM were 34.2%, 68.4% had sufficient activity, 18.4% had a risky lifestyle, and 57.9% had obesity. The results of the chi-square test showed that there was a relationship between family history and DM in women of productive age (p=0.030 and OR=0.417), physical activity (p=0.044 and OR=0437), lifestyle (p=0.001 and OR=0.120), obesity (p=0.002 and OR=3.280). Recommendation: It is hopes that Community Health Center officers, the Surveillance Teams, and the Kota Sabang Health Service can increase outreach activities regarding early detection and prevention of DM by implementing the 3Jdiet, meal planning, and checking blood sugar levels regularly at least once a month.